Peran Kualitas Pelayanan, Citra Merek dan Promosi Terhadap Kepuasan Konsumen pada Alfamart di Kecamatan Semarang Tengah - Barti Syabana Mustikasari; Vincent Didiek Wiet Aryanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study was to determine how much Alfamart customer satisfaction in the Central Semarang District is influenced by service quality, brand image, and promotional tactics. Because the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method is thought to be useful for thoroughly examining the causal link between latent components, this study employs a quantitative approach. With 385 respondents, the study population comprises all Alfamart patrons in the Central Semarang District. Online questionnaires with a five-category Likert scale were distributed to collect the research data, which were then processed using SmartPLS version 3 software. The analysis findings indicate that the quality of service provided plays an important role, brand image, and promotions contribute to providing a meaningful influence on the level of customer satisfaction. These results support efforts to boost Alfamart customer satisfaction by enhancing service quality, bolstering favorable brand perceptions, and putting in place customer-focused promotional initiatives.